Using spray-dried sugar beet molasses in ice cream as a novel bulking agent - Acan, Betul Gizem; Toker, Omer Said; Aktar, Tugba; Tamturk, Faruk; Palabiyik, Ibrahim; Konar, Nevzat (OXFORD UNIV PRESS, 2020)
In this study, it is aimed to investigate and evaluate the use of molasses which is a by-product of sugar production as a novel bulking agent in ice cream as a sugar replacer. Sugar beet molasses (75%) and 12 DE maltodextrin (25%) were converted into powder form by spray drying. Spray-dried sugar beet molasses (SDSM) was then used as a substitute of sugar in different ratios (0:100, 25:75, 50:50, 75:25 and 100:0) in the ice cream products. The increased amount of SDSM decreased the overrun, L*, whiteness index (WI) and melting behaviours and increased a*, b*, total phenolic content, consistency and viscosity. Meanwhile, thermal properties have not been affected by the use of SDSM (P < 0.05). The sensory findings have been particularly interesting especially when replacing above 50% sugar with SDSM, aroma, flavour and general acceptability decrease. According to the results of this study, substituting 25% of total sugar with SDSM as a bulking agent can decrease cost of the product and improve total phenolic content and some quality parameters without compromising sensorial properties.
Keywords: Ice cream; maltodextrin; molasses; sugar; RHEOLOGICAL PROPERTIES; QUALITY CHARACTERISTICS; SENSORY PROPERTIES; FAT REPLACERS; HYDROCOLLOIDS; FUNCTIONALITY; ATTRIBUTES; PERCEPTION; PREFERENCE; CHOCOLATE; Food Science & Technology